2018
DOI: 10.33140/ijcrt/03/02/00003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Musashi-2 and Decreased NUMB Protein Levels Observed in Human Colorectal Cancer are reverted to Normal Levels by ATRA-Induced Cell Differentiation

Abstract: Background: Musashi stem cell (SC) proteins (MSI-1 & MSI-2) are known to become over expressed during colorectal tumorigenesis in humans and mice. MSI-1 overexpression induces tumorigenesis through Notch activation via inactivation of NUMB. Previous studies also show that MSI-2 overexpression in mice induces intestinal tumorigenesis but the mechanism is independent of NUMB. However, whether the MSI-2/NUMB pathway contributes to colorectal cancer (CRC) development in humans is still undetermined. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…First, IC50 concentrations were determined for ATRA and DEAB in HT29 and SW480 cells ( Figure 1 A,B). We found that the IC50 concentration for ATRA was 10 µM for both cell lines, which is consistent with prior studies [ 7 , 23 , 25 ]. The IC50 concentrations for DEAB were 100 µM for SW480 and 1 mM for HT29.…”
Section: Resultssupporting
confidence: 92%
“…First, IC50 concentrations were determined for ATRA and DEAB in HT29 and SW480 cells ( Figure 1 A,B). We found that the IC50 concentration for ATRA was 10 µM for both cell lines, which is consistent with prior studies [ 7 , 23 , 25 ]. The IC50 concentrations for DEAB were 100 µM for SW480 and 1 mM for HT29.…”
Section: Resultssupporting
confidence: 92%